2021
DOI: 10.1007/s00787-021-01846-y
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic medication among children who experience parental death to cancer

Abstract: The psychological consequences of losing a parent to cancer are unclear. We investigated whether experiencing parental death to cancer before 18 years of age increases the risk of psychotropic medication. We used register data of all children born in Denmark between 1 January 1987 and 31 December 2016 (N = 1,488,846). We assessed rate ratios (RRs) with 95% confidence intervals (CIs) for first redeemed prescription of antidepressants, anxiolytics and hypnotics according to parental death status using Poisson mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…11,12,14 This places parents and children at risk of adverse psychosocial outcomes, to include an increased risk among children for psychotropic medication when not prepared for the death of a parent. 6,7 This lack of support from professionals is disconcerting, as it is well-established…”
Section: Discussionmentioning
confidence: 99%
“…11,12,14 This places parents and children at risk of adverse psychosocial outcomes, to include an increased risk among children for psychotropic medication when not prepared for the death of a parent. 6,7 This lack of support from professionals is disconcerting, as it is well-established…”
Section: Discussionmentioning
confidence: 99%
“… 9 We also found that the pattern of the HR over time was similar after natural and unnatural parental death, which was not clear in previous studies limited to cancer or sudden parental death. 7 , 9 …”
Section: Discussionmentioning
confidence: 99%
“… 5 There have been a few population-based studies examining parentally bereaved children and youth's antidepressant use. 6 , 7 , 8 However, none of them provided comprehensive analysis on how the risk of antidepressant initiation changed over time following parental death, although such information could be valuable for offering timely support for the bereaved child, as highlighted by a study examining 216 bereaved children over seven years. 9 Furthermore, the negative impact of parental death may also exacerbate over long term, through accumulation of stressors subsequent to the death such as family socioeconomic difficulties and other changes in family life.…”
Section: Introductionmentioning
confidence: 99%
“…Aynı zamanda ebeveyni kanser hastalığı nedeniyle ölen çocuklara psikotrop ilaç reçete etme riskinde önemli bir artış görülmektedir. Ebeveyn çocukla aynı cinsiyetteyse ve ebeveyn tanıdan sonraki bir yıl içinde öldüyse bu risk daha da artabilir (Hoeg et al, 2021). Anne ve babasını kanser hastalığından kaybeden çocuklar, özellikle hastalığın hızlı ilerlediği durumlarda ve ölümden sonraki ilk altı ayda ekstra psikolojik desteğe ihtiyaç duyabilirler.…”
Section: Psikososyal Sağlıkunclassified